CONCEPTUAL PAPER: PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Arya, Gusti Ayu Agung Deviana; Silvianita, Anita; Rubiyanti, Nurafni; Widodo, Arry (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Employee performance is the result of the work they have done. Good performance is usually caused by the application of good work principles by employees. Implementation of Good Corporate Governance (GCG) and a high level of work discipline will provide added value to employee performance. This research aims to evaluate the effect of implementing Good Corporate Governance (GCG) and work discipline on employee performance, with work motivation as a mediating variable, in one of the private companies in the trade sector of Bali Province. The population and sample of this research are all employees in the company. Data collection was carried out through interviews, direct observation and questionnaires. Data analysis used SPSS version 26 software with a quantitative approach. Keywords: Good Corporate Governance (GCG), Work Discipline, Employee Performance, Work Motivation